Volume 2: Economic, Environmental, and Policy Aspects of Alternate Energy; Fuels and Infrastructure, Biofuels and Energy Storag 2014
DOI: 10.1115/es2014-6448
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Laminar Burning Speeds and Investigation of Flame Stability of Acetylene (C2H2)/Air Mixtures

Abstract: Laminar burning speeds and flame structures of spherically expanding flames of mixtures of acetylene (C2H2) with air have been investigated over a wide range of equivalence ratios, temperatures, and pressures. Experiments have been conducted in a constant volume cylindrical vessel with two large end windows. The vessel was installed in a shadowgraph system equipped with a high speed CMOS camera, capable of taking pictures up to 40,000 frames per second. Shadowgraphy was used to study flame structures and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After solving properties of burned gases, S L can be calculated from the measured pressure time histories. The stretch effects are not considered in this study because several studies , have shown that the stretch effect approaches zero asymptotically with the increasing radius of curvature and was negligible in the constant volume method. A linear extrapolation between S L and the unburned gas temperature was used to calculate S L at an initial temperature of 428 K in a stretch-free region (see Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…After solving properties of burned gases, S L can be calculated from the measured pressure time histories. The stretch effects are not considered in this study because several studies , have shown that the stretch effect approaches zero asymptotically with the increasing radius of curvature and was negligible in the constant volume method. A linear extrapolation between S L and the unburned gas temperature was used to calculate S L at an initial temperature of 428 K in a stretch-free region (see Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Laminar burning velocity, a fundamental phenomenon in premixed combustion, plays a key role in understanding a mixture's reactivity, diffusivity, and exothermicity [16][17][18]. It is used in turbulent combustion models to study the turbulent flame propagation, emissions production, and flame morphological structure and instability.…”
Section: Introductionmentioning
confidence: 99%